Hubungan penghargaan kendiri, resilien, sikap asertif dan kempimpinan dalam kalangan “Mat Rempit” di Lembah Klang - Mohd Suhaimi Mohamad; Nasrudin Subhi; Daniella M. Mokhtar (Penerbit Universiti Kebangsaan Malaysia, 2020)
Youth faces drastic changes in their psychological, biological and social development. The involvement of adolescents in reckless motorcycle riding also known as ‘rempit’ is a social phenomenon that reflects devian behavior. Various programs have been carried out on prevention and recovery from various sectors. However, reckless motorcycle riding still occurs within our society and it has now grown to become a current trend among male youth especially those that are school dropouts to become 'Mat Rempit'. This paperwork sets out to measure the level of self-esteem, resilience, assertiveness and leadership. A quantitative design was applied in this field study. Sample recruitment were carried out via snowballing based on purposive sampling. A total of 30 youths between the age of 16 and 25 were recruited into the youth empowerment camp. Results show a significant relationship between self-esteem, resilience, assertiveness and gang leadership. There was a significant difference in terms of self-esteem (t=3.1, p<0.05) before and after the camp was carried out. Research implications were further discusses based on the impact towards the camp participants, their family, the social development of the youth and the improvement of the empowering youth-at-risk module. It is hoped that through this youth empowerment camp, participants have the potential to change risky behaviours to positive behaviours in order to contribute towards self-development and the well-being of their family.